2019
DOI: 10.1080/02640414.2019.1616958
|View full text |Cite
|
Sign up to set email alerts
|

Sprint mechanical differences at maximal running speed: Effects of performance level

Abstract: The University of Gloucestershire accepts no liability for any infringement of intellectual property rights in any material deposited but will remove such material from public view pending investigation in the event of an allegation of any such infringement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 54 publications
0
26
0
3
Order By: Relevance
“…Therefore, one of the most well researched topics to improve understanding of how quasi-stiffness is controlled during running is alterations in quasi-stiffness and other running variables with running velocity changes. Paradisis et al [ 58 ] stated that quasi-stiffness (leg and vertical) are key to generating a higher top running velocity during a short sprint. Tables 1 and 2 list the studies on vertical and leg stiffness that meet the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, one of the most well researched topics to improve understanding of how quasi-stiffness is controlled during running is alterations in quasi-stiffness and other running variables with running velocity changes. Paradisis et al [ 58 ] stated that quasi-stiffness (leg and vertical) are key to generating a higher top running velocity during a short sprint. Tables 1 and 2 list the studies on vertical and leg stiffness that meet the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Vertical stiffness increases with running velocity and stride frequency [ 33 , 55 , 58 68 ] and body mass [ 69 ]. Vertical stiffness also increases with the level of maturity [ 70 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to the EMG data (Table 2), we were not able to detect the effects of the short-latency stretch reflex on active muscle stiffness at 500 and 600 deg•s −1 in sprinters. Moreover, previous studies demonstrated that leg and joint stiffness were greater in sprinters than long-distance runners (Harrison, Keane, & Coglan, 2004;Hobara et al, 2008) and leg stiffness was significantly correlated with sprint performance (Chelly & Denis, 2001;Paradisis et al, 2019). Hobara et al (2008) indicated that the greater joint stiffness in sprinters may be attributed to differences in intrinsic properties of the musculoskeletal system rather than differences in neural activities.…”
Section: Discussionmentioning
confidence: 97%
“…The inductive sensor was able to accurately track strain with an NRMSE of 2.43% (Figure F). This test was limited in its strain rate and in comparison with the motion capture data of the intended application (Figure C), the actual frequency and strain rate required to track running was much higher—often upward of 100% s −1 (Figure C)—with a stride frequency as high as 5 Hz for a sprinter . To analyze the ability of the sensor to track fast movements, the sensor was strained at frequencies from 0.1 to 20 Hz using a sine wave pattern (Figure A,B).…”
Section: Discussionmentioning
confidence: 99%
“…The ability to track kinematics—complex body movements typically reserved for motion capture systems—with soft sensors has been growing with the development of both hardware (i.e., sensors, electronics, and wireless systems) and software (i.e., apps and neural networks) and has become increasingly accurate for complex movements . Tracking lower body movements requires sensors to track at high frequency and speeds, upward of 5 Hz for a sprinter's gait, although the body can move at a frequency beyond 10 Hz in certain circumstances such as seizures . Strain sensors that rely on geometric changes are attractive for high‐frequency applications (which would currently be reserved for OMCs and IMUs) as these sensors can be produced with highly elastic and resilient materials that are not as susceptible to hysteresis.…”
Section: Introductionmentioning
confidence: 99%